2022
DOI: 10.1371/journal.pone.0262639
|View full text |Cite
|
Sign up to set email alerts
|

Disparate participation by gender of conference attendants in scientific discussions

Abstract: One important metric of a radiologist’s visibility and influence is their ability to participate in discussion within their community. The goal of our study was to compare the participation level of men and women in scientific discussions at the annual meeting of the Radiological Society of North America (RSNA). Eleven volunteers collected participation data by gender in 59 sessions (286 presentations) at the 2018 RSNA meeting. Data was analyzed using a combination of Chi-squared, paired Wilcoxon signed-rank a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The proportion of women radiologists involved in conferences does not represent the population from which our profession is recruited or the patients we serve. The proportion of women involved in the RCRASM from 2014-2021 reflects that of RCR consultant membership (37%, 30 ), and is similar to the proportions of women presenters at the 2018 Radiological Society of North America conference (RSNA) (35% 31 ), and at the Association of University Radiologists' (AUR) and the American Roentgen Ray Society (ARRS) conferences in 2009, 2014 and 2019 (39%, 32 ).…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
See 2 more Smart Citations
“…The proportion of women radiologists involved in conferences does not represent the population from which our profession is recruited or the patients we serve. The proportion of women involved in the RCRASM from 2014-2021 reflects that of RCR consultant membership (37%, 30 ), and is similar to the proportions of women presenters at the 2018 Radiological Society of North America conference (RSNA) (35% 31 ), and at the Association of University Radiologists' (AUR) and the American Roentgen Ray Society (ARRS) conferences in 2009, 2014 and 2019 (39%, 32 ).…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
“…Previous studies have focused on a single year of a conference 31,45 , or focused on subgroups of conference presenters 45 or presenters only without assessing the gender balance of conference organising committees 19,31,32,40,45 . In contrast, our study makes use of eight years of data from the RCRASM, using information on presenters in all roles, and on the gender balance of the conference committees to give as complete a picture as possible of the patterns of involvement of women and men at all levels of the RCRASM, and to assess for changes in these patterns over recent years.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some evidence that women talk less than men in social and professional groups (Holmes, 1992;Rezaee et al, 2022). Rezaee et al (2022), in an observational study conducted at a professional conference, investigated the relationship between gender and participation.…”
Section: Gendermentioning
confidence: 99%
“…There has been some evidence that women talk less than men in social and professional groups (Holmes, 1992;Rezaee et al, 2022). Rezaee et al (2022), in an observational study conducted at a professional conference, investigated the relationship between gender and participation. The results indicated that during discussion after presentations, men participated with more frequency than women, and spoke for longer during their contributions.…”
Section: Gendermentioning
confidence: 99%